On the Design Criteria for Buried Steel Penstock of Hydropower Station - WANG Jin-long; DING Xu-liu; WU Xue-gao (Renmin Zhujiang)
Taking the buried steel penstock of a hydropower station as an example,this paper presents the criteria,methods and applications in designing the underground buried steel penstocks in Switzerland. Stress is laid on the determination of bearing capacity of the adjoining rock, the distribution of loads between the steel lining and the adjoining rock and the methods for determining the length ofsteel lining. Comparison has been made with the existing design methods adopted in China.